Zee : schilderijen en plastieken - teksten. (Rotterdam : Galerie Delta)
Benner, G. ; van Bohemen, Kees ; Claus, Hugo ; Dahmen, K. F. ; Ficheroux ; Mooy, Jaap ; Motz, Wim ; Pieters, Ian J. ; Rubington ; Schoonhoven, J.J. ; Vandercam, Serge ; Wagemaker, Jaap ; Donia, Jan ; Hyoens, Jan ; Picabia, Francis ; Holst, A. Roland ; Rubington ; Smit, Robert ; Bastiaan, Cornelius ; Verhagen, Hans
Zee : schilderijen en plastieken - teksten, Galerie Delta, Rotterdam, s.a.
boek